How Do Nocebo Phenomena Provide a Theoretical Framework for the COVID-19 Pandemic? - Amanzio, Martina; Howick, Jeremy; Bartoli, Massimo; Cipriani, Giuseppina Elena; Kong, Jian (Frontiers in Psychology, 2020)
The COVID-19 pandemic is a major health issue, which leads to psychological and behavioural changes. In particular, among various negative feelings, fear seems to be one of the main emotional reactions that can be as contagious as the virus itself. The actual pandemic is likely to function as an important stressor, especially in terms of chronic anxiety and lack of control over the succession of unforeseeable environmental events. In this direction, the psychological impact of previous quarantine measures showed important negative psychological effects, including post-traumatic stress symptoms with long-lasting effects. The presence of psychological discomfort and disturbances due to negative contextual factors can be studied using the nocebo phenomenon as a possible theoretical explanatory framework. Although in the absence of studies linking nocebo to Covid-19 and data-driven evidence, the context of the actual pandemic may be seen as a fertile ground for amplified discomfort and anxiety. The media provide dramatic and negative descriptions and often present conflicting sources of information, which can lead to physical and mental health problems, diminishing response to treatment. This can be worse when supported by conspiracy theories or misinformation. The aim of this perspective review is to propose a new theoretical framework for the COVID-19 pandemic, which should be supported by future empirical studies. In particular, the negative contextual factors, which can predispose individuals to psychological distress, and the onset of the nocebo phenomena will be presented here, in order to suggest possible guidelines to mitigate the devastating effects of COVID-19.